Lanthanide sulfate frameworks: Synthesis, structure, and optical properties - Bunlawee Yotnoi (2018)
Layered lanthanide sulfate compounds with three different structures have been prepared and characterized. The compounds [C10H10N2][La(SO4)2]·2H2O (I), [C10H10N2][La(SO4)2(H2O)2]2(IIa), [C10H10N2][Pr(SO4)2(H2O)2]2(IIb), [C10H10N2][Nd2(SO4)4(H2O)2]2(IIIa), [C10H10N2][Sm2(SO4)4(H2O)2]2(IIIb), and [C10H10N2][Eu2(SO4)4(H2O)2]2(IIIc) have anionic lanthanide sulfate layers separated by protonated bipyridine molecules. The layers are formed by the connectivity between the lanthanide polyhedra and sulfate tetrahedra. The formation of a two-dimensional La-O-La layer (Ia), Pr-O-Pr chains (IIb), and a tetramer cluster (IIIa) is noteworthy. The compounds exhibit honeycomb (I), square (IIa, IIb), and honeycomb (IIIa-IIIc) net arrangements, when the connectivity between the lanthanide ions is considered. Optical studies indicate the observation of characteristic metal-centered emission at room temperature. The Nd compound (IIIa) exhibits a two-photon upconversion behavior.(Figure Presented) © 2011 American Chemical Society.